2019
DOI: 10.1021/acsomega.9b00707
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine-Modified Polymer as an Efficient Palladium Scavenger and Effective Catalyst Support for a Functional Heterogeneous Palladium Catalyst

Abstract: The polyethyleneimine-modified polymers, polystyrene–divinylbenzene-based (TAs) and polymethacrylate-based polymers (TAm), were used as palladium scavengers to eliminate residual palladium species after palladium on carbon-catalyzed Sonogashira-type coupling reaction. Since both TAs and TAm indicated relatively favorable elimination abilities toward residual palladium species in the reaction mixture, the affinities of TAs and TAm for palladium species were used as supports for palladium catalysts. The TAm-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Hybrid materials have also been used to recover precious metals (e.g., Pd, Au, Pt). Previous studies have reported a high-recovery material based on a polymer consisting of thiocarbonyl groups for metal coordination and amino groups for hydrophilicity . Gelation occurred through self-assembly between the thiocarbonyl groups and metal ions, precipitating the self-assembled polymer–metal complexes, which were then separated by filtration (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials have also been used to recover precious metals (e.g., Pd, Au, Pt). Previous studies have reported a high-recovery material based on a polymer consisting of thiocarbonyl groups for metal coordination and amino groups for hydrophilicity . Gelation occurred through self-assembly between the thiocarbonyl groups and metal ions, precipitating the self-assembled polymer–metal complexes, which were then separated by filtration (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…A promising field, particularly in pressure-driven processes, is organic solvent nanofiltration (OSN) [ 3 ]. Lab-scale and commercial-scale applications of OSN membranes have been reported [ 4 , 5 ]. In the advance and application of the membrane process, characterization of modelling and optimization are essential steps [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished through screenings of dozens of potential workup protocols and scavengers, among other purification techniques. This process generates several dozens of samples in which to quantify palladium. Meanwhile, new scavengers continue to emerge, , adding options to explore.…”
Section: Introductionmentioning
confidence: 99%